Islamic microfinance as a panacea for poverty alleviation - Jimoh, Abdulrazaq; Bamigbade, Dayo; Kolawole, Kayode (European Journal of Islamic Finance, 2024)
Islamic microfinance is a tool for promoting financial inclusion and reducing poverty levels. Countries such as Nigeria has scanty empirical investigations in this regard. This calls for a more robust analysis. This study, therefore, investigated the influence of the Islamic microfinance system on poverty alleviation in Kwara State, Nigeria. Non-probability, purposive sampling was adopted to select traders and small business owners from the weekly-market setting of selected towns/villages in the three senatorial districts of Kwara State. Five (5) markets were selected from each of the three (3) senatorial districts. Data were collected with a structured questionnaire and analyzed with descriptive and inferential statistics. Ordered Logistic Regression was conducted. It was found that qard al hasan (0.91, p<0.05) murbah (0.72, p<0.01), mudharaba (0.51, p<0.1) musharaka (0.17, p<0.05) had a positive, significant effect on income level. It was also found that qard al hasan (0.38, p<0.05) murbaha (0.63, p<0.01), mudharaba (0.15, p<0.05) musharaka (0.59, p<0.01), zakat (0.45, p<0.01) and sadaqa (1.35, p<0.01) had a positive, significant effect on the productivity level. The study concluded that micro-credit, micro-equity and charity (social finance) products significantly influenced poverty alleviation. An adequate supply of shariah-compliant micro-credit, micro-equity and charity financial resources was recommended to boost the productivity and income levels of low-income earners and small business owners in the State. Also, the Central Bank of Nigeria (CBN) is encouraged to provide enabling environment for formal non-interest microfinance to promote financial inclusion and reduce poverty in the country.